(untitled) - Dr.Sayeda Meharunisa (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2021)
This paper is based on the Social Dimensions of Sustainability of Education due to Climate Change. Thus the whole research is done as in quest of reforming MENA region to an utmost importance and to an utmost important place and position as in par with other absolutely developed nations in the world. In this paper emphasis is put on how the climate change effects the education of MENA region. .The effect of COVID-19 on the income is also discussed. Moreover the impact of this on the education of MENA region is also presented. Many solutions are thought of such as a vision that envisages the world and that vision is as with all its success and that is, the 2030 Vision. We will try to study what happens due to climate change in the education. Moreover we will also study how sustainable development of education and educational development should be established in MENA region.